Basal cell carcinoma- a prospective clinico epidemiological and pathological study - Ammasaigoundan, V.; Shariff, V. N. S. Ahamed; Ramesh, A. (International Journal of Research in Medical Sciences, 2017)
Background: Basal cell carcinoma is the most common malignant tumour of the skin worldwide. The objective was to find out the age and sex incidence of basal cell carcinoma in patients attending the outpatient department of dermatology and to find out the various clinical and histopathological features of basal cell carcinoma. Methods: It was a prospective observational study carried out in a tertiary care hospital, Chennai, Tamilnadu, India. Patients with clinical diagnosis of basal cell carcinoma were included in the study after thorough history, clinical examination, routine and special investigations like skin biopsy. Results: Out of 20 patients with basal cell carcinoma 6 were males and 14 were females with a male to female ratio of 1:2.33. Most commonly affected age group was 50-70 years (70%). Distribution of BCC in our study was confined to head and neck area. Most common morphological subtype encountered in this study was nodular/nodulo-ulcerative BCC (70%), followed by pigmented type (25%) and superficial BCC (5%). The most common histological variant observed in present study was nodular type (55%), followed by pigmented variant (25%), adenoid (5%), basisquamous (5%), superficial BCC (5%) and BCC with sebaceous differentiation (5%). Conclusions: This study highlights a paradoxically increasing trend of BCC with female predilection. Early detection and treatment of lesions are crucial to decrease the functional and cosmetic disfigurement and also this study highlights the importance of improving awareness among general practitioners, public health workers and general population.